Parents’ practices and beliefs about their infants play at two state infant mental health clinics in Cape Town - Domingo, Marchelle (Stellenbosch : Stellenbosch University, 2021)
ENGLISH SUMMARY : Background: Insight into local beliefs about play, which is highly under studied within the first three years of life, could inform clinical practice in that clinicians and parents might have different views about play. Aim: The study aimed to explore and describe parents’ practices and beliefs about their infants play. Methods: Qualitative study using individual semi structured interviews with six purposefully selected parents, who attended an Infant Mental Health Clinic at either Tygerberg or Lentegeur state hospitals in Cape Town, over the last twelve months. Results: All parents were birth parents, with a mean age of 33 years. Most parents (83.3%) were female. Two-thirds (66.7%) were unemployed at the time of the interview. Infants were predominantly male (83.3%). Most parents had never considered play as something of significance in their own or their children’s lives. Several transgenerational subthemes emerged, suggesting that parents’ experiences and beliefs about play impacted their interaction and the messages they conveyed about play behaviours. Most parents appeared motivated to give their children the best opportunities for play, but some found it difficult to balance daily demands and demonstrated a reliance on expert guidance. Conclusions: There is a need for parental guidance – to allow for a space for parents to explore what they understand by ‘play’ and what their childhood experiences might have been, before the clinician can give information, examples, and guidance as to the importance of play so that it can be meaningful for the parent.